Just-in-case to justified irrigation: Applying co-innovation principles to irrigation water management. (June 2017) - Srinivasan, MS; Bewsell, D; Jongmans, C; Elley, G
A pilot study, using a co-innovation approach in identify opportunities to improve irrigation management, is underway in five farms in an irrigation scheme in New Zealand. Through a process of co-learning, a group of on-farm and off-farm stakeholders defined the problem of on-farm water use efficiency and co-developed solutions to enhance farmers' ability, desire and capacity to adopt improved irrigation practices. To enable informed decision-making, participants were supplied with current soil water demand (measured on farm) and 2- to 15-day rainfall forecasts as a daily email update. We conducted several one-on-one formal/informal meetings and annual workshops with stakeholders to evaluate the farmers' ability in integrating the updates into their current irrigation practices. Selected key findings were (i) on-farm irrigation decisions are influenced by on-farm and off-farm hydrological, climatic, infrastructural and regulatory factors, thus we need to develop a wider view to irrigation management, (ii) for successful uptake, it is important to understand the external stimuli that directly and indirectly conflict or align with proposed practice changes, (iii) introduction of stakeholders with conflicting perspectives needs to be carefully managed, (iv) with co-learning, project objectives continuously evolve in response to ongoing monitoring, review and reflection on the processes, thus it is important to build flexibility into the implementation pathway and (v) when scaling out from five farms to the wider irrigation scheme, opportunities such as collective learning and reflection at end-user focused workshops may become more challenging owing to stakeholder numbers, thus other co-learning opportunities need to be identified.